Research of PSCAD software system opportunities for adequate simulation of automatic voltage regulators with forced control of synchronous generators; Интеллектуальные энергосистемы; Т. 3 - Askarov A. B. Alisher Bakhramzhonovich (Релейная защита, автоматика, электрооборудование электроэнергетических систем, 2016)
Заглавие с титульного экрана